Barrier options model for estimate firm´s probabilities for financial distress - Milanesi, Gastón S. (2016)
Assimilation of the capital value as a call option over firm’s assets allows to develop a group of dynamic models to predict corporate financial distress. However, the concept shows an important weakness: the direct and positive relationship between the capital value (call) with the level of underlying’s volatility. This reasoning indicates that the higher the risk is, the higher the value must be for the firm, leading to a weak rationality, in particular to estimate probabilities of financial distress. The exotic barrier options make an alternative approach for predicting financial distress, and its structure fits better to the firm valuevolatility relationship. The paper proposes a “naive” barrier option model, because it simplifies the estimation of the unobservable variables, like firm asset’s value and risk. First, a simple call and barrier option models are developed in order to value the firm’s capital and estimate the financial distress probability. Using an hypothetical case, it is proposed a sensibility exercise over period and volatility. Similar exercise is applied to estimate the capital value and financial distress probability over two firms of Argentinian capitals, with different leverage degree, confirming the consistency in the relationship between volatility-value-financial distress probability of the proposed model. Finally, the main conclusions are shown.